THE STUDENTS’ PERCEPTIONS ON USING E-POSTER IN MASTER THESIS FINAL VIVA PRESENTATION - Bella Fatimah Lukman; Akmal Akmal (PROJECT (Professional Journal of English Education), 2023)
Joint Thesis Writing Program is the flagship program between Universitas Ahmad Dahlan and some overseas universities, such as Universitas Teknologi Mara and the University of Saint Anthony. It has final presentation called Final Viva. Final Viva is one of the academic final project presentations for students joining the Joint Thesis Writing Program. One of the media used in Final Viva is E-Poster. Final Viva presentation in batch 17 is the first batch that using E-Poster. Therefore, this research was conducted to explore students' perceptions about using E-Posters as a media to present their thesis. The aims of this research are to know students’ perception using E-Poster as media to presentation, to investigate their difficulties when using E-Poster, and to describe their solutions to overcome the obstacles. Six participants who were students of the Joint Thesis Writing Program in collaboration with Mara University of Technology and Saint Anthony University. Based on the result E-Posters are ease media to use for an academic presentation. In addition, they also get its use in conveying their ideas. On the other hand, there was also participant who expressed a negative perception that they did not feel helped by the E-Poster, considering that the space was very limited. Behind the ease and usefulness of using E-Posters as media for presentations, they still find difficulties, such as in compiling an E-Poster and using it. However, they also have their ways to overcome the difficulties.